Avaliação da Política Nacional de Saúde da Pessoa Idosa na gestão municipal de Fortaleza-Ce. - Maia, Sandra Maria Pontes (2010)
Increased life expectancy and population aging are global trends, the sharp demographic transition is a fact that requires analysis of the elderly as subject and collective rights. The Brazilian legislation has advanced significantly in the field of social protection to the elderly segment on the national scene and established legal rights that ensure the elderly be treated as accountability and beneficiary of the Government, therefore the target of public policies that allow ease the difficulties and improve the this age group. The aim of this study is to evaluate the implementation of National Health Policy of the Elderly-PNSPI in municipal management of Fortaleza, from 2008, under the approaches of administrative decentralization and intersectoral approach. We opted for evaluative research of qualitative approach was used as instruments for data collection of unstructured interviews and semi-structured field diary and secondary data collection. The scenario study was designed from the Municipal Health Secretariat and the Regional Executive Secretariats of Fortaleza-CE. The cast of actors of this analysis is the technical PNSPI operationalize the regional and municipal levels of Fortaleza- CE. He added himself to the study interviews with experts of the federal and the state of Ceará, which allowed a contextual analysis of the implementation of PNSPI from the national to local level. The study followed the ethical standards established by resolution 196 of the National Health Council, Ministry of Health Data analysis was based on analysis of structure, process and outcome, using the technique of critical discourse analysis, which allowed the study of significance, for spheres of power, the National Health Policy of the Elderly in the course management hierarchy, from national level, through municipal and state level, reaching the regional executive level. As main results the study showed that the absence of a municipal budget, specific to the health of the elderly, coupled with lack of a uniform and systematic information in the administrative decentralized, difficult to establish internal consistency of services and actions the elderly population in Fortaleza. The research identified as fundamental the action of health professionals, regional and local authorities, and intersectoral and multidisciplinary teams in the process of operationalizing the PNSPI in municipal management of Fortaleza, from 2008. The study concluded that it is essential to overcoming current limitations identified to achieve the proper enforcement of the National Health Policy for the Elderly in Fortaleza.